Nickel Hydride Catalyzed Cleavage of Allyl Ethers Induced by Isomerization - Kathe, Prasad M.; Berkefeld, Andreas; Fleischer, Ivana (Synlett, 2021)
This report discloses the deallylation of O- and N-allyl functional groups by using a combination of a Ni-H precatalyst and excess Brønsted acid. Key steps are the isomerization of the O- or N-allyl group through Ni-catalyzed double-bond migration followed by Brønsted acid induced O/N–C bond hydrolysis. A variety of functional groups are tolerated in this protocol, highlighting its synthetic value.
Keywords: nickel catalysis; deprotection; allylic ethers; isomerization; selectivity